Green building application technology of student apartment in Central Plains area -Take Xinzheng City as an example - YunLiang, Niu; Azhaili, Baharun; Mohd Afzan, Mohamed (Ministry of Education, china and Northeastern University, china., 2024)
With the global pursuit of sustainable development goals, green building technology has attracted increasingly more attention in the construction of student apartments in the Central Plains of China. This study takes Xinzheng student apartment as a case to explore the application status, challenges and development strategies of green building technology. Through the field investigation and case analysis of several student apartment projects in Xinzheng City, we identified the key problems in the design and construction, such as low energy efficiency, low resource utilization and poor living environment quality. The study proposes a series of optimized design and construction management strategies based on BIM technology, aiming to improve energy efficiency, resource utilization and living comfort. In addition, through the modular design research of prefabricated steel structure student apartment, this paper presents an efficient student apartment design scheme. The results show that the adoption of green building technologies and strategies can not only significantly improve the living comfort and energy efficiency of student apartments, but also achieve cost saving economically and promote the sustainable development of the project.